The Story of drawing an alternative history of art - Owens, Susan 19XX- (Yale University Press, 2024)
Drawing is at the heart of human creativity. The most democratic form of art-making, it requires nothing more than a plain surface and a stub of pencil, a piece of chalk or an inky brush. Our prehistoric ancestors drew with natural pigments on the walls of caves, and every subsequent culture has practised drawing - whether on papyrus, parchment or paper. Artists throughout history have used drawing as part of the creative process.While painting and sculpture have been shaped heavily by money and influence, drawing has always offered extraordinary creative latitude. Here we see the artist at his or her most unguarded. Susan Owens offers a glimpse over artists' shoulders - from Michelangelo, Rembrandt and Hokusai to Van Gogh, Käthe Kollwitz and Yayoi Kusama - as they work, think and innovate, as they scrutinise the world around them or escape into their imaginations.The Story of Drawing loops around the established history of art, sometimes staying close, at other times diving into exhilarating and altogether less familiar territory